Assessment of concrete strength by combined nondestructive methods for normal and high performance concrete - Ashiru, Babandede Mohammad (2007)
This Study deals with Non Destructive Testing (NDT) for both Normal and High Performance Concrete (HPC). An experimental study was carried out, involving both destructive and non destructive methods applied to different concrete mixes, with compressive strength of 30, 40, 50, 60 and 70 MPa. The cubes use were 100mm x 100mm x 100mm. Model were choose from the literature and the strength Prediction Model for the HPC using UPV, Normal Concrete using UPV , generalized strength Prediction Model for Normal and HPC using Sclerometer and lastly combined generalized model were validated by the data obtained from the present study. Data were plotted in order to estimate the percentage of error that was given by the model. The results show Strength prediction model using Sclerometer test is a generalized model. Strength prediction model using UPV method could not be generalized and therefore, two different models were used for normal and high performance concrete. The combined NDT model that is combined of Sclerometer and UPV method gave a power model and implied generalized.